Accomplishment of Danish International Development Agency (DANIDA) on Actualizing Energy Democracy in Central Java with Environmental Support Programme Phase-3 (ESP-3) Program - Alam, Surya (Department of International Relations Universitas Pertamina, 2022)
This research analyses the energy democracy in Central Java conducted by the Danish International Development Agency (DANIDA) in the Environmental Support Programme Phase 3 (ESP-3) scheme. This research aims to explain DANIDA's effort to actualize energy democracy through the outcome of a clean energy management project in Central Java within four chosen regions, i. e. Semarang City, Cilacap Regency, Klaten Regency, and Karimunjawa Islands. In order to analyse this problem, the writer used energy democracy as an effort to achieve equity in energy access. Qualitative methods are used in this research, emphasizing the use of secondary data, including earlier research, official documents, and related archives, using primary data from interviews with related informants. This research shows that DANIDA can actualize energy democracy in Central Java, manifesting Denmark's commitment to global environmental problem mitigation. Two indicators of energy democracy, such as popular sovereignty and participatory governance, proved from local community satisfaction response by local government involvement and the increase of energy supply which fulfilled the needs. The third indicator, civic ownership, including ownership of access, was not seen clearly; however, the local community acquires access availability. Those indicators, therefore, become the benchmark of DANIDA's accomplishment of energy democracy in Central Java.